2008
DOI: 10.1177/1363460708091742
|View full text |Cite
|
Sign up to set email alerts
|

Dude-Sex: White Masculinities and `Authentic' Heterosexuality Among Dudes Who Have Sex With Dudes

Abstract: Based on examination of an online community in which white `str8'-identified men assert that sex with other white men bolsters their heterosexual masculinity, this article examines the heterosexual and racialized meanings that white str8 dudes attach to their same-sex behaviors. The study points to the role of whiteness in the process of establishing heterosexual `realness', or believable straight culture. Findings indicate that for the white str8 dude, Black male bodies disrupt the staging of normal `male bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 8 publications
(9 reference statements)
7
140
1
1
Order By: Relevance
“…A parallel manifestation of racial preference was also uncovered in sections of the user's profiles that allowed the user to describe preferences in their own words. Statements such as "typically prefer white guys" (Tanner) and "Safe fun with young fit guys prefer white guys but not opposed to others" (Benno) coincide with those of other scholars who found that gay culture is not only gendered, but also can be particularly racialized (Ocampo, 2012;Ward, 2008).…”
Section: Instances Of Networked Masculinities In Desired Partnerssupporting
confidence: 60%
See 2 more Smart Citations
“…A parallel manifestation of racial preference was also uncovered in sections of the user's profiles that allowed the user to describe preferences in their own words. Statements such as "typically prefer white guys" (Tanner) and "Safe fun with young fit guys prefer white guys but not opposed to others" (Benno) coincide with those of other scholars who found that gay culture is not only gendered, but also can be particularly racialized (Ocampo, 2012;Ward, 2008).…”
Section: Instances Of Networked Masculinities In Desired Partnerssupporting
confidence: 60%
“…The policing among male groups demonstrates Connell's (2005) claim that hegemonic masculinity is not restricted to power relations between genders but also explores power relations within genders (Demetriou, 2001, Ward, 2008. Within the hegemonic masculine lens, gay men are not excluded for their sexuality alone, but for the fact that their sexuality does not contribute to the patriarchal order (Demetriou, 2001).…”
Section: Gay Masculinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on hybrid masculinities has also sought to identify ways in which men's practices, styles, and behaviors incorporate elements of femininity as well as subordinated masculinities such as black men's language style or dress or gay men's aesthetic (Barber, 2008;Bridges, 2014;Bridges & Pascoe, 2014;Ward, 2008). Rather than see this adoption of new practices as a sign of progress and equality, however, scholars using the term hybrid masculinity are critical of the power dimensions that might allow some men to maintain privilege through these reconfigurations of masculinity.…”
Section: Shifting Masculine Ideals-inclusivity and Hybriditymentioning
confidence: 99%
“…Theories on heteronormativity could be useful in studies that deal with identity, family life, relationships and intimacies in selfidentified heterosexuals (see Archakis & Lampropoulou, 2009;Kitzinger, 2005;Magnusson, 2006;Ward, 2008). When heteronormativity is drawn on in studies on self-identified nonheterosexuals, it is shown that non-heterosexuals are construed as 'other' or 'deviant' (see Land & Kitzinger, 2005).…”
Section: Queer Theory and Heteronormativitymentioning
confidence: 99%